Effectiveness of the European semester: Explaining domestic consent and contestation - Aleksandra Maatsch (Max Planck Institute for the Study of Societies, 2017)
Do parliamentary parties politicize compliance within the European Semester? If so, which conflict lines organize parliamentary debates? In order to address these questions, this discussion paper analyses national parliamentary participation in two budgetary cycles of the European Semester (2014 and 2015) in Austria, France, Germany, and Ireland. While in France and Germany, compliance within the European Semester has been subject to strong politicization, this has not been the case in Austria and Ireland. Moreover, strong politicization coincided with the contestation of country-specific recommendations among the parliamentary parties. The empirical analysis established that strong formal powers in budgetary matters constitute an important prerequisite allowing parliamentary parties to articulate their contestation. However, the willingness to comply depends most directly on whether the content of country-specific recommendations is coherent with the economic preferences of a political party, not the government-opposition cleavage. – – Wird compliance im Rahmen des Europäischen Semesters durch nationale Parteien politisiert? Falls ja, entlang welcher Konfliktlinien orientieren sich parlamentarische Debatten? Um diese Fragen anzugehen, analysiert dieser Artikel die Beteiligung nationaler Parlamente in zwei Budgetzyklen des Europäischen Semesters (2014 und 2015) in Österreich, Deutschland, Frankreich und Irland. Während in Deutschland und Frankreich compliance im Rahmen des Europäischen Semesters verstärkt Gegenstand von Politisierung war, trifft dies in Irland und Österreich nicht zu. Darüber hinaus wurden in den Fällen mit starker Politisierung verstärkt auch Anfechtungen der länderspezifischen Empfehlungen durch die parlamentarischen Parteien festgestellt. Die empirische Analyse zeigt, dass starke formale Befugnisse in Budgetangelegenheiten eine wichtige Voraussetzung für Parlamente darstellen, länderspezifische Empfehlungen anzufechten. Allerdings hängt die Bereitschaft, den länderspezifischen Empfehlungen zu folgen, in großem Ausmaß davon ab, ob diese inhaltlich mit der zugrunde liegenden ökonomischen Haltung der Partei übereinstimmt und nicht von der Kluft zwischen Regierung und Opposition.
hdl:11858/00-001M-0000-002C-E924-3
Keywords: 300; European economic governance; the European Semester; national parliaments; politicization; compliance; europäische Wirtschaftspolitik; das Europäische Semester; nationale Parlamente; Politisierung; compliance